Women in the Religious Modernity Movement: A Study of the Community of Veiling Women in Lombok - Arianingsih, Fadhilatillaili (Lembaga Yasin AlSys, 2025)
This research examines women in the religious modernity movement by studying Lombok's veiled women's community. Specifically, this research discusses the forms of veiled women's movements amid modernity, which are analyzed using the Resource Mobilization Theory. The researcher uses a qualitative approach with a case study method that focuses on the experiences and views of veiled women in the socio-religious Movement. The research type used is field research using a qualitative descriptive approach. The research subjects were the founders, leaders, and administrators of Lombok's veiled women's community. Data collection techniques in this research used observation, interview, and documentation methods. The research results indicate that the veiled women's community in Lombok is a socio-religious movement that provides social benefits to the community. In addition, the veiled women's community in Lombok is also used as a symbol of the Movement and has succeeded in becoming a public figure and example for the surrounding community. It can be seen from the success of various community programs that the community on Lombok Island has welcomed.